2022
DOI: 10.3389/fpsyg.2022.891778
|View full text |Cite
|
Sign up to set email alerts
|

Research of the Changes in the Psychological Status of Chinese University Students and the Influencing Factors During the COVID-19 Pandemic

Abstract: BackgroundPsychological dynamics of college students have changed during the COVID-19 outbreak but little research has been done in this area. The purpose of this study is to investigate the dynamic changes in the mental health status of college students since the outbreak of the COVID-19 pandemic 1 year and the influencing factors.MethodsThe research period was from February 2020 to August 2021. 384 college students were analyzed three times during this period on the recognition and psychological state of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Some studies have shown that college students are more likely to have strong stress reactions than ordinary employees in the face of the COVID-19 pandemic and related measures, such as online learning and remote employment [ 4 ]. Compared with male college students, female college students have been more susceptible to the external environment during the pandemic [ 5 , 6 ] and are more likely to rely on others to help them [ 4 , 7 ]. This, together with the more severe employment pressure faced by female college students [ 8 ], has resulted in a greater health threat to female college students [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that college students are more likely to have strong stress reactions than ordinary employees in the face of the COVID-19 pandemic and related measures, such as online learning and remote employment [ 4 ]. Compared with male college students, female college students have been more susceptible to the external environment during the pandemic [ 5 , 6 ] and are more likely to rely on others to help them [ 4 , 7 ]. This, together with the more severe employment pressure faced by female college students [ 8 ], has resulted in a greater health threat to female college students [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, over 41 million students were enrolled in higher educational institutions [2], and college students were more likely to experience anxiety and depression, with 15% of Chinese college students suffering anxiety symptoms [3]. As the outbreak was effectively contained, students' mental health improved slightly [4], but the closed management of most campuses also contributed to mental health issues among college students.…”
Section: Introductionmentioning
confidence: 99%